SELECTIVE INHIBITION OF THE WEST NILE VIRUS METHYLTRANSFERASE BY NUCLEOSIDE ANALOGS - Chen, Hui (2012)
The flavivirus methyltransferase (MTase) sequentially methylates the N7 and 2’-O positions of the viral RNA cap (GpppA-RNA→m(7)GpppA-RNA→m(7)GpppAm-RNA), using S-adenosyl-L-methionine (SAM) as a methyl donor. We report here the synthesis and biological evaluation of a series of novel nucleoside analogs. Two of these compounds can effectively and competitively inhibit the WNV MTase with IC(50) values in micromolar range and, more importantly, do not inhibit human MTase. The compounds can also suppress the WNV replication in cell culture.